Use of polylactic acid in face lipodystrophy in HIV positive patients undergoing treatment with antiretroviral drugs (HAART) - Onesti, M G; Renzi, L F; Paoletti, F; Scuderi, N (Acta chirurgiae plasticae, 2004)
OBJECTIVES: The recent use of antiretroviral drugs in people with HIV infection produced a drastic reduction in mortality and a remarkable improvement in the quality of life for these patients. However the aesthetic and psychological consequences that come from the reorganization of the adipose tissue induced by these drugs (facial wasting, buffalo hump) may reduce this state of wellbeing. METHODS: Our group, in cooperation with the 3rd Division of Infective Diseases of the University of Rome "La Sapienza", decided to evaluate the efficacy of polylactic acid (PLA) in combating these problems in HIV positive patients undergoing treatment with antiretroviral drugs in an evaluating study of 4 cases. The evaluation of the obtained results was performed by follow-up at one, three, six and twelve months from the first infiltration and considering the clinical evaluation, the photographical documentation and the patient's judgement. RESULTS: In all cases we obtained an improvement of the local condition with the restoration of a more booming aspect. The change was noted both within the family and the work environment. In the first three cases the results were considered as optimal by both the operators and the patients. In the fourth case the result was evaluated as discreet (a remarkable loss of weight of the patient in the months following the treatment should be taken into consideration). CONCLUSIONS: We think a new study with ultrasonography of dermal thickness before, during and after the treatment is necesary. This study will give a more reliable evaluation of the product efficacy.
Keywords: Humans; syndrom lipodystrofie spojený s HIV; Antiretroviral Therapy, Highly Active; lidé středního věku; Polyesters; HIV infekce; Lactic Acid; HIV Infections; obličej; Female; dospělí; lidé; polymery; Biocompatible Materials; Adult; Polymers; ženské pohlaví; polyestery; Male; Middle Aged; vysoce aktivní antiretrovirová terapie; HIV-Associated Lipodystrophy Syndrome; biokompatibilní materiály; Face; mužské pohlaví; kyselina mléčná